A New Inequality for Frames in Hilbert Spaces. (3rd October 2018) - Xiang, Zhong-Qi
Abstract : We obtain a new inequality for frames in Hilbert spaces associated with a scalar and a bounded linear operator induced by two Bessel sequences. It turns out that the corresponding results due to Balan et al. and Găvruţa can be deduced from our result.